Lietuvių, rusų ir vokiečių istoriografija Lenkijos ir Lietuvos unijos klausimu - Jučas, Mečislovas (Lietuvos istorijos studijos, 1997)
The investigations in the Poland-Lithuania union were carried out first in Polish and Russian historiography and later in the Lithuanian one. During the 30-40's the latter studies dealt with the earliest pre-union Lithuanian history and emphasized the independent, long-lasting monarchy and the Lithuanian statehood inside the union. Signing the Krėva treaty in 1385, Jogaila did not think about incorporating Lithuania into Poland but intended to rule both states by himself. Thus, in 1385, only a personal inter-state relationship was stated (A. Šapoka). After the restoration of an independent Lithuanian ruler dynasty in 1392, Jogaila possessed no power in Lithuania and did not issue any documents (K. Jablonskis). The rule of Jogaila and his heirs in Lithuania was interrupted. Such a situation remained unchanged until the Lublin union, which did not abolish the Lithuanian state but constituted the union of two states (A. Šapoka, K. Avižonis, B. Dundulis). However, after the Lublin union, Lithuania was left "with limited statehood" (J. Jakštas). The 17th and 18th centuries were the centuries of rapprochement rather than merging of two states and two political nations (A. Šapoka). During Soviet times, Lithuanian historiography, influenced by Russian historians' works, evaluated the Lublin union negatively, describing it as the burial of the Lithuanian state, the intensification of noble privileges, and an obstacle to social progress (J. Jurginis).Russian historiography appropriated the Lithuanian state and called the Grand Duchy of Lithuania the West Russian state, the continuation of the Kiev state in the territory of Western Russia. According to this historiography, the biggest part of the territory and population belonged to the Russian ethnos. Its early Christianization and, consequently, written language and spiritual culture gave priority to the Eastern part of that state. The political life, under conditions of full decentralization, was determined by the federation of regions (mainly Russian ones). The disputes concerned only the nature of the ethnos: whether it was Russian or Byelorussian during the 15th and 16th centuries. Russian historiography was unanimous about the Lublin union, which interrupted the natural development of the Lithuanian state and subordinated Lithuania to the political, cultural, and religious interests of Poland. Liberation came only in 1795 when the Grand Duchy of Lithuania was incorporated into the Russian Empire.The parliamentary union was treated from the point of view of Russian researchers who investigated the early state of Lithuania. M. Lubavski studied the diet of the Grand Duchy of Lithuania until 1569. He treated the parliamentary history of the 15th and 16th centuries as a growth of political consciousness of noblemen and, consequently, their search for greater political rights together with the Polish szlachta. So, the real union came in 1569. V. Pičeta dealt with the economic and social system. Thus, he stated that the real union was determined by the estate privileges and the Lithuanian noblemen's strive for consolidation and increase of these privileges following the Polish szlachta. Meanwhile, J. Lappo was interested in the Russian ethnos, and his estimation of the union was based on it.German historians considered that the Lithuanian state was formed in the ethnic Lithuanian territory and the Russian annexation came later. However, Lithuania showed religious tolerance in the Russian territories and provided them with a wide self-government (H. Jablonowski). German historians agreed that the union created a two-state Poland-Lithuania state—Doppelreich (J. Pfitzner, G. Rhode, M. Bockmann, S. Ekdahl). Some of them (G. Rhode, H. Gersdorf) thought that the union was initiated by Poles and was not directed against the German Order, with which Poland had no conflict since 1343. In 1385, the Poles represented the interests of "Poloniae Minoris." It was only M. Hellmann who thought that the union was in one way or another directed against the German Order. He emphasized the significance of the union for the whole Central Europe. K. Forstreuter pointed out the late Christianization of Lithuania and its importance. Thus, the union was more important in cultural rather than political respect. Poland was wiser in solving this problem than the German Order, which approved only armed force against pagans (Heidenkampf). Lithuania remained in that noble Republic (Adelsrepublik) only because it was under the Russian cultural influence and regained its cultural peculiarities (K. Lemack). However, during the 17th and 18th centuries, Lithuania remained in the shadow of Poland and had limited self-government (M. Hellmann, K. Zemack).